One-lung flooding reduces the ipsilateral diaphragm motion during mechanical ventilation. Issue 1 (December 2016) - Lesser, Thomas; Schubert, Harald; Güllmar, Daniel; Reichenbach, Jürgen; Wolfram, Frank
Abstract Background Diaphragm motion during spontaneous or mechanical respiration hinders image-guided percutaneous interventions of tumours in lung and upper abdomen. Motion-tracking methods can be applied but increase procedure complexity and procedure time. One-lung flooding (OLF) generates a suitable acoustic pathway to lung tumours and likely suppress diaphragm motion. The aim of this study was to quantify the effect of OLF on ipsilateral diaphragm motion during contralateral one-lung ventilation. Methods To measure the diaphragm motion, M-mode ultrasonography of the right hemidiaphragm was performed during spontaneous breathing and mechanical ventilation, as well as after right-side lung flooding, in three pigs. Diaphragm motion was analysed using magnetic resonance images during left-side lung flooding and mechanical ventilation, in four pigs. Results Double-lung ventilation increased the diaphragm movement in comparison with spontaneous breathing (17.8 ± 4.4 vs. 12.2 ± 3.4 mm, p  = 0.014). Diaphragm movement on the flooded side during contralateral one-lung ventilation was significantly reduced compared to that during double-lung ventilation (3.9 ± 1.0 vs. 17.8 ± 4.4 mm, p  = 0.041). By analysing the magnetic resonance images, the hemidiaphragm on the flooded side showed an average displacement of 4.2 mm, a maximum displacement of 15 mm close to the ventilated lung and no displacement at the lateral side. Conclusion OLF leads to a drastic reduction of diaphragm motion on the ipsilateral side which implies that targeting and motion compensation algorithms for interventions like high-intensity focused ultrasound ablation of intrapulmonary and hepatic lesions might not be required.